Bromocriptine quick‐release as adjunct therapy in youth and adults with type 1 diabetes: A randomized, placebo‐controlled crossover study. Issue 11 (25th July 2022) - Tell, Shoshana S.; Schafer, Michal; Vigers, Timothy; Baumgartner, Amy D.; Lyon, Ellen; Gross, Susan; Polsky, Sarit; Snell‐Bergeon, Janet K.; Schauer, Irene E.; Nadeau, Kristen J.
Abstract: Aim: To evaluate the potential for glycaemic, renal and vascular benefits of bromocriptine quick release (BCQR) in adolescents and adults with type 1 diabetes. Materials and Methods: Forty adolescents and 40 adults with type 1 diabetes aged 12‐60 years old were enrolled in a double‐blind, placebo‐controlled, random order crossover study of 4 weeks of treatment in the morning with BCQR (titrated weekly from 0.8 mg to 1.6 mg to 3.2 mg, minimum dose 1.6 mg). Study assessments after each phase included blood pressure (BP), lipids, peripheral arterial stiffness and autonomic function, mixed meal tolerance test, continuous glucose monitoring (CGM), creatinine, estimated glomerular filtration rate, estimated insulin sensitivity, insulin dose and indirect calorimetry. Results: Adolescents displayed baseline hyperglycaemia, insulin resistance, metabolic dysfunction and increased renal filtration compared with adults. In both age groups, continuous glucose monitoring measures, estimated insulin sensitivity and insulin dose did not differ with BCQR treatment. In adolescents, BCQR decreased systolic BP, diastolic BP and triangular index and increased serum creatinine. In adults, systolic BP, mean arterial pressure, systemic vascular resistance, and mixed meal tolerance test glucose and glucagon‐like peptide 1 areas under the curve were lower, and the orthostatic drop in systolic BP was greater with BCQR. Conclusions: Greater hyperglycaemia, insulin resistance, metabolic dysfunction and renal hyperfiltration in adolescents argues for increased attention during this high‐risk age period. Although BCQR had little impact on glycaemia or insulin sensitivity, initial vascular and renal responses suggest potential benefits of BCQR in adolescents and adults with type 1 diabetes requiring further study.